2007
DOI: 10.1158/1055-9965.epi-06-1058
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Relation between Biomarkers for Smoking and Biomarkers for Acrylamide Exposure in Humans

Abstract: Smoking is an important source of acrylamide exposure in the general population. We assessed the relationship between hemoglobin adducts of acrylamide (HbAA) and glycidamide (HbGA) as biomarkers of acrylamide exposure and plasma cotinine (PC) as biomarkers of tobacco smoke exposure in 94 men and 67 women. The median (5th-95th percentile) biomarker concentrations (pmol/g Hb) in the group of individuals with PC concentrations of V10 ng/mL were 51 (29-155) and 34 (16-117) for HbAA and HbGA, respectively. They wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 41 publications
7
34
0
3
Order By: Relevance
“…Increased tremor has been found among smokers or snuffers compared to non-smokers/non-snuffers (29). Cigarette smoking is also a source of acrylamide exposure (30)(31)(32), although acrylamide neurotoxicity due to smoking alone is not clinically relevant (32). The proportion of current smokers was comparable in the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Increased tremor has been found among smokers or snuffers compared to non-smokers/non-snuffers (29). Cigarette smoking is also a source of acrylamide exposure (30)(31)(32), although acrylamide neurotoxicity due to smoking alone is not clinically relevant (32). The proportion of current smokers was comparable in the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Because smoking is an important source of acrylamide exposure (21,22), we conducted subgroup analyses for never smokers. All P values presented are two-sided and P < 0.05 was considered statistically significant.…”
Section: Cancer Epidemiol Biomarkers Prev 2009;18(6) June 2009mentioning
confidence: 99%
“…Subsequentlly, a number of studies by several investigators have demonstrated that carcinogenic compounds, especially those present in cigarette smoke (e.g., the tobacco-specific nitrosamines and 4-aminobiphenyl), bind covalently to hemoglobin (110)(111)(112)(113)(114). Hemoglobin presents itself as an ideal target for the interaction of various xenobiotics.…”
Section: Resultsmentioning
confidence: 99%